Development of a Three Tier Test Instrument to Identify Student Misconceptions in Class V Science Subjects - Vidiyauni, Asri; Andriana, Encep; Pamungkas, Trian (LPPM Universitas Primagraha, 2021)
This study was designed to develop a three-level test instrument so that it can be used to evaluate student learning outcomes and assess students' understanding of concepts, not understand concepts or improve misconceptions in natural science subjects in the human circulatory system. This research was conducted until February 2020. The validation of the instrument was carried out on three validators, material experts, linguists, and calculation experts with an average level of eligibility obtained at 80.16% in the feasible category. Retrieval of research data was carried out at the Tangerang district genIUS School and obtained several students about misconceptions with the highest level of misconception occurring in the concept of the heart and lungs.